2008
DOI: 10.3349/ymj.2008.49.2.255
|View full text |Cite
|
Sign up to set email alerts
|

Agreements between Indirect Calorimetry and Prediction Equations of Resting Energy Expenditure in End-Stage Renal Disease Patients on Continuous Ambulatory Peritoneal Dialysis

Abstract: PurposeEquations are frequently used to estimate resting energy expenditure (REE) in a clinical setting. However, few studies have examined their accuracy in end-stage renal disease (ESRD) patients.Materials and MethodsTo investigate agreement between indirect calorimetry and several REE estimating equations in 38 ESRD patients on peritoneal dialysis, we performed indirect calorimetry and compared the results with REEs estimated using 5 equations [Harris-Benedict (HBE), Mifflin, WHO, Schofield, and Cunningham]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
10
0
2
Order By: Relevance
“…Application of commonly used predictive equations in clinical practice (i.e., Harris-Benedict Equation (HBE), Schoenfeld, Mifflin-St Jeor (MJSE), etc.) have been studied on a limited basis in CKD, and have produced conflicting results, e.g., under- or over-estimation of energy requirements when compared to the mREE obtained by IC (8, 11, 20). Consequently, existing predictive energy equations are not reliable for use in CKD, and especially among those patients on MHD (11).…”
Section: Introductionmentioning
confidence: 99%
“…Application of commonly used predictive equations in clinical practice (i.e., Harris-Benedict Equation (HBE), Schoenfeld, Mifflin-St Jeor (MJSE), etc.) have been studied on a limited basis in CKD, and have produced conflicting results, e.g., under- or over-estimation of energy requirements when compared to the mREE obtained by IC (8, 11, 20). Consequently, existing predictive energy equations are not reliable for use in CKD, and especially among those patients on MHD (11).…”
Section: Introductionmentioning
confidence: 99%
“…However, Lee et al . () found a significant overestimation only with Mifflin St Joer. Based on the research of Shah et al .…”
Section: Discussionmentioning
confidence: 87%
“…Interestingly, one study found all predictive energy equations, Schofield, WHO and Harris Benedict, to significantly overestimate energy needs while the other study found only Mifflin St Joer to exceed energy needs (p < 0.05) (Lee et al . ; Dias Rodrigues et al . ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Há ainda outras equações também referenciadas em artigos científicos 33,34 , mas menos empregadas 35,36 . 31 , FAO-1985 32 e FAO-2001 (ou de Schofield) 11 foram desenvolvidas a partir de análise de regressões de estudos que avaliaram a TMB de diferentes populações.…”
Section: Equações De Predição Da Tmb E Do Getunclassified